Safe and improved analgesia following bupivacaine with epinephrine infiltration before skin graft harvesting - Chee Kwan, Kong (2015)
Introduction: Skin grafting is the commonest surgical procedure performed to cover soft tissue defects. It has been known that the split skin graft donor site is more painful than the recipient site itself. Despite its frequent usage, the donor site preparation and postoperative protocol has not been standardized. Infiltration of lignocaine (or / in addition with bupivacaine) is consistently performed prior to harvesting of skin graft only if done under local anaesthesia. However it is not practiced routinely if skin harvesting was done under general anaesthesia. This prospective study determined the benefit and risk of bupivacaine with epinephrine infiltration before harvesting skin graft under general anaesthesia. Method: Sixty patients admitted to University Malaya Medical Centre (UMMC) from July 2012 to April 2013 who required split skin graft from thigh as part of their management were randomized using online randomization tool into either the infiltration group or no infiltration group. Post-operatively, all the patients were given patient-controlled analgesia (PCA) morphine for at least 24 hours to monitor morphine requirement. The Visual analog scale (VAS) assessment was started after 8 hours postoperatively then continued till 24 hours. Total consumption of patient-controlled analgesia morphine was charted every 4 hours to monitor consumption of opioid analgesia for breakthrough pain. Results: Only 53 of the 60 (88.3%) recruited subjects participated in the research until completion (27 in the infiltration group while 26 in the no infiltration group). No statistical difference in the distribution between gender, age, ethnic group, indication for skin graft and estimated donor size among the two randomized groups. There was significant difference in pain intensity between the two groups from 8 to 20 hours post-operatively (p <0.05). The difference between the two groups on cumulative usage of PCA morphine was also significant from 8 to 16 hours post-operatively. There was no neuro-cardiotoxicity detected in both group of patients. None of the donor sites was infected and all healed completely by one month review. Conclusion: Subcutaneous infiltration of bupivacaine with epinephrine before harvesting of split skin graft under general anaesthesia improved postoperative analgesia and decreased opioid consumption. No sign of any toxicity or wound infection observed. It is a safe procedure in the selected group of patients. Therefore, this technique is strongly recommended to be routinely practised to improve postoperative care of skin graft patients.